Do Institutional Quality and Oil Prices Matter for Economic Growth in Russia: An Empirical Study - Bass, Alexander (International Journal of Energy Economics and Policy, 2018)
In this article we aim to assess the impact of institutional quality and world oil prices on performance of Russian manufacturing sector. Based on the data for the period 1996-2017 for Russia we explore the relationship between institutional quality, measured by the corruption perception index, world oil prices (Brent) and performance of Russian GDP using a VEC framework. For detecting the casual relationship, Granger causality test is applied. The results of the study show that oil prices, institutional quality and economic growth in Russia are cointegrated in the long-run. Yet short-run effects are statistically insignificant. Results of Granger causality test show unidirectional causality running from oil prices and institutional quality to economic growth. Keywords: oil prices, economic growth, institutional quality, vector autoregression JEL Classifications: D02, E01, L60, O13, Q41 DOI: https://doi.org/10.32479/ijeep.7091